Anti-corruption strategies in the South African public sector : perspectives on the contributions of complexity thinking and ICTs - Habtemichael, Faniel Sahle (Stellenbosch : University of Stellenbosch, 2009)
Thesis (PhD (School of Public Management and Planning ))—University of Stellenbosch, 2009.